THE SOCIALLY INCLUDED OR EXCLUDED? THE EXPERIENCES OF OLDER PEOPLE LIVING ALONE - Rapolienė, Gražina; Mikulionienė, Sarmitė; Gedvilaitė-Kordušienė, Margarita; Jurkevits, Anastasiya (Socialinė teorija, empirija, politika ir praktika, 2018)
While there is a tendency to study regularities in the social exclusion of older people, the distinctive feature of this article is the aim to reveal the subjective assessments of social participation of elderly people who live alone. Social exclusion/inclusion is defined in the article as a multiple concept describing (un)just social relationships. An analysis of the data from the original empirical research (27 semistructured interviews) reveals a wide range of social exclusion cases experienced at various levels. In line with the social justice scheme, the narratives of social exclusion are based on personal and interpersonal contexts (age, health, communication, autonomy), as well as the organizational, community (work) and broader social context (participation in events and politics).
Keywords: experiences of social inclusion/exclusion; older people living alone; qualitative research